Design-build Projects: New Urban Experiences through Short-term Spatial Experiments (EAAE Annual Conference Proceedings, 2025)
Practical urban research and new spatial experiences in the form of short-term experiments, hands-on construction, informal atmosphere, and co-learning define the approach of architectural summer schools. These non-formal, design- build programs have evolved into a distinct pedagogy, often implemented by architecture, design, and art schools through institutional partnerships. Back in 2008, architects and educators J. Anderson and C. Priest launched the Live Projects program at the School of Architecture at Oxford Brookes University and co-founded the Live Projects Network that promotes this approach in architectural education and practice and currently it serves as a catalogue and wide reference base for such projects. However, integrating these hands-on learning experiences into formal curricula remains a challenge for many universities.Formal architectural education often lacks engagement with real-world needs and users. Students do not acquire enough practical construction skills and knowledge of current materials and techniques, and remain confined in the classroom. These observations led to the establishment of the Summer School of Ephemeral Architecture and Spatial Design in Latvia. Titled FestivaL’and, it has been running since 2018 in collaboration with the Summer Theater Festival and the Municipality of Valmiera. FestivaL’and explores contemporary, short-term architectural and spatial design interventions as catalysts for rethinking city spaces. During the camp, participants gain knowledge, skills and experience in the process of design creation, from research, ideation, tectonic experimentation to hands-on 1:1 scale timber construction techniques. Interventions often take place in abandoned buildings, underused spaces, or inactive peripheries. These are approached through cultural-historical analysis and participatory design methods, with the goal of proposing temporary architectural solutions that activate the sites and help evaluate their future potential. The interventions function as placemaking pilots that test spatial possibilities, foster inclusivity, and engage the local community. The structure of the summer school allows for flexibility, experimentation, and immediate public feedback. The paper will reflect on FestivaL’and’s six cases striving to bridge informal education with formal curricula, learning and envisioning urban transformations.